Perceived stress and appearance anxiety among people with acne vulgaris - Anupama Priyamkari; Anil Kakunje; Manjunath Mala Shenoy (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Acne vulgaris is a chronic inflammatory, pilosebaceous condition. It is one of the world's most common skin diseases, affecting millions of patients. The frequency and length of the acne may not represent explicitly the psychological condition of a patient. This research was aimed at measuring perceived stress and anxiety of appearance among people with acne vulgaris. MATERIALS AND METHODS: It is a cross-sectional, observational study, carried out at tertiary care teaching hospital following approval by the Institutional Ethics Committee. Seventy-five outpatients with acne vulgaris were included in the study and the perceived stress scale (PSS) and appearance anxiety inventory (AAI) administered to them. RESULTS: There were 55 females and 20 males among the 75 acne patients. The mean age of the study patients was 23.55 ± 3.83. The mean duration of the acne was 3.35 years. The mean PSS was 19.48 ± 6.44 among the patients. The total AAI score among all the patients was 13.67 ± 5.67. The avoidance AAI score was 7.09 ± 4.5 and the threat AAI score was 5.82 ± 3.35. As the mean duration increased, the level of the stress was also increased. CONCLUSION: The results show that the PSS and AAI have psychometric properties to decide whether improvements in cognitive processes and behaviors mediate outcomes in patients. The duration of acne vulgaris had a direct positive association with the higher PSS and AAI score.